Understanding proto-insurgencies - Byman, Daniel, 1967- (Rand counterinsurgency study ;, 2007)
To gain the size and capabilities of an insurgency, a would-be insurgent movement must create a politically relevant identity; it must espouse a cause that is popular beyond the group; it must gain dominance over rival organizations; and it must find a sanctuary that provides respite from police, intelligence, and military services. Violence is instrumental in all the tasks proto-insurgencies seek to accomplish. However, violence can also backfire on them, since few people support it. Support from outside states offers numerous advantages to groups seeking to become insurgencies. It can provide safe haven, money, training, and help with political mobilization. It can also help groups overcome logistical difficulties, hinder intelligence-gathering against them, and legitimize them, making government delegitimization efforts almost impossible. Outside states, however, often deliberately try to control or even weaken the group and at times can reduce its political popularity. The reaction of the state is often the most important factor in a movement's overall success. Perhaps the best and most efficient way to prevent proto-insurgents from gaining ground is through in-group policing, since groups know their own members and can enable arrests or other forms of pressure. The government can also promote rival identities. Governments must, however, recognize the proto-insurgents' weaknesses and avoid overreaction that may inadvertently strengthen them. The most obvious action for the United States is to anticipate the possibility of an insurgency developing before it materializes. It can also provide behind-the-scenes training and advisory programs and can help inhibit outside support.